Carotid Artery Stenosis in Head and Neck Cancer Patients Treated with Radiotherapy - Banu, Ramesh; Surendran, Divya; Nagarajan, Murugaiyan; Maniyarasu, Janarthanan (Indian Journal of Medical and Paediatric Oncology, 2025)
Radiotherapy (RT) is a crucial treatment modality for 80% of head and neck cancer (HNC) patients, often combined with surgery or chemotherapy, leading to a significant reduction in cancer-related mortality. However, as cancer survival rates increase, therapy-related complications also increase, impacting both mortality and morbidity. One such late complication is radiation-induced carotid artery stenosis (CAS), a condition associated with an increased risk of cerebrovascular events. Radiation-induced CAS is rarely studied, especially in the Indian population. Despite its potential severity, there is no standardized screening or management protocol for radiation-induced CAS in HNC patients.This study aims to assess the prevalence, risk factors, complications, management, and outcomes of CAS in HNC patients who received RT, with or without chemotherapy and surgery at our institution.This is a retrospective observational study of newly diagnosed primary HNC patients who received RT between January 2012 and December 2021. Patients with metastatic HNC and those treated elsewhere were excluded. Data on demographics, tumor characteristics, treatment, and imaging for vascular stenosis were collected. Statistical analysis was performed using R version 4.4.1, with categorical variables analyzed using the chi-square or Fisher's exact test and continuous variables using the Mann–Whitney's U test. Significance was set at p-value </= 0.05.Of 949 patients, 34 (3.6%) developed CAS. Preradiation vascular stenosis was rare (0.1%). Among the 34 patients categorized by time since treatment, CAS developed in 47.1% of patients after 5 years, 32.4% within 2 to 5 years, and 5.9% within 1 year. CAS severity included near-total occlusion in 23.5%, ≥70% stenosis in 20.6%, and neurological deficits in 8.8%. The median age was 62 years, and the majority were male (85.3%). Common risk factors were hypertension (29.4%), diabetes (20.6%), tobacco use (82.4%), and alcohol consumption (41.2%). Tumors of oral cavity and hypopharynx were more common. Most CAS patients (76.5%) received radical chemoradiation. Only 23.3% of CAS patients received anticoagulation therapy, with 14.3% undergoing mechanical thrombectomy.This study highlights the prevalence of radiation-induced CAS in HNC patients, especially in the Indian population, and identifies associated risk factors. Hence, standardized screening and management protocols for CAS are crucial for improving long-term outcomes in HNC survivors.
Keywords: carotid artery stenosis; head and neck cancer; radiotherapy; cerebrovascular events